2013
DOI: 10.1098/rspb.2013.0485
|View full text |Cite
|
Sign up to set email alerts
|

Early play may predict later dominance relationships in yellow-bellied marmots (Marmota flaviventris)

Abstract: Play has been defined as apparently functionless behaviour, yet since play is costly, models of adaptive evolution predict that it should have some beneficial function (or functions) that outweigh its costs. We provide strong evidence for a long-standing, but poorly supported hypothesis: that early social play is practice for later dominance relationships. We calculated the relative dominance rank by observing the directional outcome of playful interactions in juvenile and yearling yellow-bellied marmots (Marm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 56 publications
0
59
1
Order By: Relevance
“…Similarly, an evaluation of fi eld data on yellow baboons reveal that early life play behaviour predicts both early and prospective wellbeing (Pereira and Fairbanks 1993 ). More recently, it was documented that social dominance in adulthood is related to juvenile play in yellow-bellied marmoths (Blumstein et al 2013 ). Rate of social play shows a positive relation with subsequent reproductive success in ground squirrels (Nunes et al 2004 ) and feral horses that spend more time playing were having a higher survival rate (Cameron et al 2008 ).…”
Section: Evolution Of Playmentioning
confidence: 98%
“…Similarly, an evaluation of fi eld data on yellow baboons reveal that early life play behaviour predicts both early and prospective wellbeing (Pereira and Fairbanks 1993 ). More recently, it was documented that social dominance in adulthood is related to juvenile play in yellow-bellied marmoths (Blumstein et al 2013 ). Rate of social play shows a positive relation with subsequent reproductive success in ground squirrels (Nunes et al 2004 ) and feral horses that spend more time playing were having a higher survival rate (Cameron et al 2008 ).…”
Section: Evolution Of Playmentioning
confidence: 98%
“…However, a study of yellow-bellied marmots has demonstrated a link between play outcomes in pups and dominance rank as yearlings, which attenuates over time (so that the association almost vanishes by the time they are adults) (Blumstein et al, 2013). The precise mechanism by which play predicts later rank is as yet unknown.…”
Section: What Factors Hasten the Initial Rise To Alpha Status?mentioning
confidence: 99%
“…In species where both sexes disperse and groups consist of related and unrelated individuals, social bonds develop early in the ontogeny and greatly influence dominance rank, dispersal decision and reproductive success in adults of both sexes (e.g. [24,25]). Some species are monogamous because males are not able to monopolize more than one female [26,27].…”
Section: Introductionmentioning
confidence: 99%